2014
DOI: 10.1007/978-3-662-44426-9_23
|View full text |Cite
|
Sign up to set email alerts
|

Is the Public Motivated to Engage in Open Data Innovation?

Abstract: Part 3: Policy and StakeholdersInternational audienceGovernments aim to increase democracy by engaging the public in using open data to develop mobile apps and citizen services. They make information available (open data) and organize innovation contests to stimulate innovation with the goal to make new services available for the public to use. But will the public take on the challenge to both develop and provide services to each other? In this paper we use a case study from public transportation to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…There is rich evidence stating that OGD has the potential to drive innovation [1], [9], [10], [36], it allows for increased levels of transparency [1], helps drive the creation or implementation of new public services [1], [4], [9], [36] and helps empower citizens and communities [1]. However, there are also barriers that seem to inhibit these benefits from manifesting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is rich evidence stating that OGD has the potential to drive innovation [1], [9], [10], [36], it allows for increased levels of transparency [1], helps drive the creation or implementation of new public services [1], [4], [9], [36] and helps empower citizens and communities [1]. However, there are also barriers that seem to inhibit these benefits from manifesting.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also barriers that seem to inhibit these benefits from manifesting. Some of the main barriers in the literature include issues with data quality [1], [2], [3], [36], lack of government willpower [1], [2], [3], [11], [26], confidentiality issues [5], [10], [12], and absence of understanding of OGD [1], [3], [11], [13], [36]. It is clear that OGD may be used to drive innovation and change how public services are created.…”
Section: Introductionmentioning
confidence: 99%
“…We include six publications which are deemed relevant for this study (see Table 3). Based on the selected papers, we observed that many factors influence citizens to engage with OGD or to engage in an open data hackathon: intrinsic motivations such as fun and enjoyment and intellectual challenge [12]; extrinsic motivations concerning performance expectancy [13] or relative advantage [16], learning and developing skills, and networking [11,12]; effort expectancy [13] related to ease of use [17]; social influence [13,18] including contributing to societal benefits [11,18]; and data quality [18].…”
Section: A Framework For Analyzing Citizens' Motivations To Engage Inmentioning
confidence: 99%
“…Although research on the socio-technical conditions of OGD utilization, both enabling and disabling factors, has been widely established [10], yet only a handful of studies investigate the drivers of citizen engagement in open data hackathons [11]. Previous research showed that citizens' motivations to participate in hackathons are heterogeneous [12]. For instance, in a Swedish hackathon on public transportation, the motivation is primarily associated with fun and enjoyment [12], while in a Brazilian city hackathon, contributing to solutions of social problems and networking are the main drivers [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation